2020
DOI: 10.1186/s12935-020-1118-1
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lncRNA SNHG16 suppresses multiple myeloma cell proliferation by sponging miR-342-3p

Abstract: Background: Aberrant expression of long non-coding RNAs (lncRNAs) is closely associated with development and prognosis of human cancers. LncRNA SNHG16 is reportedly involved in human cancer; however, its roles in multiple myeloma (MM) remain unclear. Methods: In this study, we investigated the function and molecular mechanisms of SNHG16 in MM. MM cells were transfected with si-SNHG16 or si-NC. SNHG16 expression levels was measured by qRT-PCR. Cell proliferation was monitored using the MTS. Flow cytometry assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…At second, we probed into the mechanism of magnolol. It has been discovered that miR miR-342-3p and miR-124-3p are involved in suppression of MM [41][42][43][44][45][46]. The same results were also performed in detection of Cyclin D1, MMP-7 and MMP-9 protein expression levels through western blot.…”
Section: Discussionmentioning
confidence: 92%
“…At second, we probed into the mechanism of magnolol. It has been discovered that miR miR-342-3p and miR-124-3p are involved in suppression of MM [41][42][43][44][45][46]. The same results were also performed in detection of Cyclin D1, MMP-7 and MMP-9 protein expression levels through western blot.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, the knockdown of LINC01234 increases miR-124-3p and suppresses GRB2 expression, resulting in a decrease of cell proliferation and the inhibition of MM growth. These results demonstrate that lncRNAs play an important role in the pathobiology of MM ( Table 1 ) [ 13 , 33 , 34 , 35 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 48 , 50 , 51 , 53 , 56 , 57 , 58 , 59 , 62 , 69 , 72 , 78 , 79 , 81 , 82 , 83 , 84 , 85 , 86 , 88 , 90 , 91 , 92 , 94 , 95 , 96 , 97 , 107 ].…”
Section: Role Of Lncrnas In the Pathobiology Of MMmentioning
confidence: 83%
“…However, an increasing number of studies in MM are showing that lncRNAs can regulate or can be regulated by more than one miRNA, such as H19 (H19 imprinted maternally expressed transcript), UCA1 (urothelial cancer associated 1) or OIP5-AS1 (OIP5 antisense RNA 1). Remarkably, there are cases like TUG1 (taurine up-regulated 1) and H19 that are associated with the regulation of the same miRNA, miR-29b-3p ( Table 1 ) [ 33 , 39 , 42 , 44 , 45 , 51 , 53 , 57 , 58 , 59 , 60 , 72 , 81 , 82 , 83 , 88 , 90 , 91 , 94 , 95 , 96 ]. These results highlight the relevance of the miRNA sponge function of lncRNAs in MM.…”
Section: Role Of Lncrnas In the Pathobiology Of MMmentioning
confidence: 99%
“…A large amount of research has shown that lncRNAs play an important role in the transcription pattern and functioning of MM. For example, knockdown of lncRNA SNHG16 significantly inhibits the proliferation of MM cells, suggesting that SNHG16 is a new therapeutic target for MM (14). In addition, lncRNA NEAT1 is highly expressed in MM samples, and silencing this gene can enhance the effect of traditional chemotherapy (15).…”
Section: Introductionmentioning
confidence: 99%